Cytotoxicity, anti-tumor effects and structure-activity relationships of nickel and palladium S, C, S pincer complexes against double and triple-positive and triple-negative breast cancer (TNBC) cells. (1st July 2021) - Hosseini-Kharat, Mahboubeh; Rahimi, Rahmatollah; Alizadeh, Ali Mohammad; Zargarian, Davit; Khalighfard, Solmaz; Mangin, Loïc P.; Mahigir, Nasim; Ayati, Seyed Hasan; Momtazi-Borojeni, Amir Abbas
Graphical abstract: Highlights: Synthesis of a series of SCS-type pincer complexes of nickel and palladium. Cytotoxicity effect of complexes against estrogen-dependent and triple negative breast cancer. Employing palladium complexes for inhibiting TNBC 4 T1 cells adhesion and migration. Abstract: Triple-Negative Breast Cancer (TNBC) is a highly aggressive form of breast cancer. The high rate of metastasis associated with TNBC is attributed to its multidrug resistance, making the treatment of this metastatic condition difficult. The development of metal-based antitumor agents was launched with the discovery of cisplatin, followed by the development of related antitumor drugs such as carboplatin and oxaliplatin. Yet, the severe side effects of this approach represent a limitation for its clinical use. The current search for new metal-based antitumor agents possessing less severe side effects than these platinum-based complexes has focused on various complexes of nickel and palladium, the group 10 congeners of platinum. In this work, we have prepared a series of SCS-type pincer complexes of nickel and palladium featuring a stable meta-phenylene central moiety and two chelating but labile thioamide donor moieties at the peripheries of the ligand. We have demonstrated that the complexes in question, namely L 1 NiCl, L 1 NiBr, L 1 PdCl, L 2 PdCl, and L 3 PdCl, are active on the proliferation of estrogen-dependent breast tumor cells (MCF-7 and MC4L2) and triple-negative breast cancer (4 T1). Among the complexes studied, the palladium derivatives were found to be much safer anticancer agents than nickel counterparts; these were thus selected for further investigations for their effects on tumor cell adhesion and migration as well. The results of our studies show that palladium complexes are effective for inhibiting TNBC 4 T1 cells adhesion and migration. Finally, the HOMO and LUMO analysis was used to determine the reactivity and charge transfer within the compounds.